Mappemonde projectee sur l'Horizon de Paris et de son Antipode. Mappemonde sur la Projection Polaire.: Dresse par A. Brue, Geographe. Reoue par E. Levasseur, Membre de l'Institut, Institut Geographique de Paris. Ch. Delagrave. Editeurs de la Societe de Geographie. 58 Rue des Ecoles. Atlas Universel en 67 feuilles No. 18. - Brué, Adrien-Hubert, 1786-1832 (Cartographer); Levasseur, Émile, 1828-1911 (Cartographer)
Two world maps with different projections, one centered around the horizon of Paris, the other centered around the North and South Pole. The hand coloured maps depict geologic terrains and ocean basins/watersheds, respectively. Relief shown by hachures. Atlas Universel De Geographie Physique, Politique, Ancienne Et Moderne, Contenant Les Cartes Generales Et Particulieres De Toutes Les Parties Du Monde . Dresse par A. Brue, Geographe. Nouvelle Edition Revue Par E. Levasseur . Comprenant 66 Cartes Et 85 Cartouches Tenant Lieu D'Autant De Cartes. Institut Geographique De Paris. Charles Delagrave, Editeur De La Societe De Geographie De Paris, 58, Rue Des Ecoles, 58. 1875 Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .